Penggunaan ChatGPT Dalam Meningkatkan Keterampilan Menulis Mahasiswa Di Kabupaten Aceh Barat - Keumala Fadhiela ND; Andrisman Satria; Chaira (CV. Multi Kreasi Media, 2025)
The ability to write is a very important skill for students in order to support academic and professional activities. However, many students now face various problems in writing, namely difficulties in organizing ideas, grammar, and writing structure. This service program aims to improve students' writing skills through training using ChatGPT, a text-based artificial intelligence model. Implementing the program involves several stages: preparation, training, writing practice, mentoring, and evaluation. A total of 25 students from various universities in West Aceh District participated in this activity. The training included introducing ChatGPT technology, practising writing text using ChatGPT features, and evaluating text writing results before and after training. The activity results showed a significant improvement in the quality of student texts, especially regarding text structure, clarity of ideas, and language use. The evaluation showed that 85% of the participants were able to write more structured texts and experienced an improvement in terms of writing grammar by 90%. In addition to improving their technical skills, the training also positively impacted students' confidence in writing. However, there were some obstacles, including initial technical challenges and potential dependency on the technology. Therefore, the use of ChatGPT should be understood as a tool to support the learning process, not as a substitute for technical skills.